(untitled) (Bioscience Journal, 2015)
In maize breeding programs can arise difficulties in relation to combination capacity studies for determination of heterotic groups, which are highly correlated with genetic divergence among the parents. The aim of this study was to estimate the genetic divergence measured for nine quantitative morphological traits in eleven single-cross hybrids of maize cultivated in the Cerrado-Pantanal ecotone. The experiment was conducted at Universidade Estadual de Mato Grosso do Sul - University Unit of Aquidauana. The experimental design was a randomized blocks with four replications. At harvest time, it were measured the following traits: plant height, ear insertion height, ear length, ear diameter, stem diameter, number of kernels per rows, number of rows per ear, weight of hundred grains and grain yield. In the application of hybrids cluster technique was adopted the Mahalanobis’s generalized distance as dissimilarity measure, and for establishment of similar groups was applied the Tocher’s method. The results indicated the existence of genetic variability among tested hybrids. The greatest genetic divergence was observed among the pairs MAXIMUS and XB6012, implying in heterotic gains. Crossings of lines extracted from hybrids 2B587HX and XB6012 with lines obtained from the other hybrids provide greater heterosis. The traits grain yield and ear insertion height were those who more and less contributed, respectively, for genetic divergence among hybrids.